(untitled) (Global Journal of Science Frontier Research, 2023)
Potatoes have received a reputation as being a large consumer of nutrients such as nitrogen N phosphorus P and potassium K An experiment was conducted to study the effect of integrated nutrient management on the dry matter accumulation and uptake of nutrients in potato Solanum tuberosum L Application of 50 RDF 50 FYM Azotobacter Phosphobacteria T 7 recorded maximum total dry matter production 21 67 which was on per with T 3 20 53 and followed by T 4 19 79 T 5 19 19 T 9 18 55 and T 6 18 42 during rabi 2011 Similarly the maximum uptake of N 97 17 kg ha P 21 76 kg ha and K 159 63 kg ha was found with plants provided with 50 RDF 50 FYM Azotobacter PSB T 7 which was on par with T 4 T 3 and T 5 during rabi 2011 The minimum dry matter accumulation 15 32 and N 83 40 kg ha P 16 13 kg ha and K 108 23 kg ha was registered with 100 FYM 50 N supplied through neem cake Azotobacter T 8